Amino acids and their derivatives in catalytic cyclohexane oxidation - Супрун, Олександр Олександрович; Реутський, Віктор Володимирович; Іващук, Олександр Сергійович; Мудрий, Сергій Олександрович (Eastern-European Journal of Enterprise Technologies, 2014)
Homogeneous catalytic oxidation of cyclohexane can be improved by using additives to industrial catalysts that are based on variable valence metals. Recent studies have been much focused on enzymatic catalysis with protein-based enzymes that consist of amino acids of various structures. We assume that the presence of two functional groups in amino acids enables them to form complexes with catalysts, function as modifiers, and influence the composition of reaction products. The present study reveals how the liquid-phase homogeneous catalytic oxidation is affected by binary catalyst systems that are composed of cobalt naphthenate and amino acids of various origins (glycine or aminosulfonic acid) as well as individual catalyst, which is cobalt salt 2 (heptadecane olamine) of pentadion acid (CSHPA). The research determines and compares qualitative and quantitative impacts of amino acid additives and individual CSHPA on the oxidation process. The study identifies the regular dependence of CSHPA catalyst on the nature of its previous ultrasound processing. It has been found that the origin of an additive and the alteration of its concentration in a catalytic system permit regulating the quantitative composition of reaction products that result from the liquid-phase oxidation of cyclohexane. The researched catalytic systems can be applied in production to improve its technical and economic indices.